'Astrophysics: history and theory', an undergraduate, interdisciplinary, asynchronous astrophysics course taught in the physics program. (1st July 2022) - Trout, Joseph J; Jacobsen, Tara; Buondonno, Gracie; Weber, Courtney
Abstract: This project produced an online astronomy course based on the free, online OpenStax textbook. When this project was conceived, about a year before the Covid-19 pandemic, the authors had no idea that in a short period of time, most college and university classes would be online. This abrupt change in modalities of courses, from traditional, face-to-face lectures and laboratories to a more modern online format, sparked energetic discussions about the effectiveness of online courses. This paper describes the online astronomy course and its creation and evaluates the success of the course at conveying the concepts and theories studied in astronomy courses. The success of this course is examined using a 100-question pre-test and post-test based on content knowledge. A survey was also completed of the students to evaluate the perceived success of the online course and the acceptance of online courses. The survey was adjusted to include opinions about the in-person labs that were cancelled due to the Covid-19 pandemic.